2017
DOI: 10.1093/jpepsy/jsx090
|View full text |Cite
|
Sign up to set email alerts
|

The Stability and Influence of Barriers to Medication Adherence on Seizure Outcomes and Adherence in Children With Epilepsy Over 2 Years

Abstract: Assessing for specific adherence barriers over time may lead to identification of interventions that result in improved adherence and care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 37 publications
3
15
1
Order By: Relevance
“…However, to our knowledge, this is the first study to systematically assess barriers to adherence in this patient population. Our results are consistent with previous studies exploring barriers to adherence in children and parents of children with chronic medical conditions including asthma, cystic fibrosis, sickle cell disease, and epilepsy 32,47‐49 . These studies demonstrated high prevalence of individual barriers and the majority of parents and patients report more than one barrier to adherence.…”
Section: Discussionsupporting
confidence: 92%
“…However, to our knowledge, this is the first study to systematically assess barriers to adherence in this patient population. Our results are consistent with previous studies exploring barriers to adherence in children and parents of children with chronic medical conditions including asthma, cystic fibrosis, sickle cell disease, and epilepsy 32,47‐49 . These studies demonstrated high prevalence of individual barriers and the majority of parents and patients report more than one barrier to adherence.…”
Section: Discussionsupporting
confidence: 92%
“…For the control group, objective adherence continued to decline over the duration of the study indicating that poor adherence to medication may not improve without intervention. A similar trend has been reported for those with poor medication adherence, without targeted intervention, in other chronic conditions [12,26,27].…”
Section: Discussionsupporting
confidence: 79%
“…In addition, real or perceived side effects, low medication literacy, and/or poor medication taste were identified as adherence barriers in cSLE. Unfortunately, adherence barriers are stable and unlikely to improve without interventions [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Barriers to adherence are modifiable variables that demonstrate consistent associations with nonadherence and suboptimal clinical outcomes in pediatric populations [9, 10]. Among children with epilepsy, barriers such as difficulties swallowing medications, forgetfulness and refusing to take medications as prescribed have been longitudinally associated with electronically-monitored nonadherence [11]. The stability of barriers to adherence has also been documented in children with newly diagnosed epilepsy, suggesting that once a barrier is endorsed, it is likely to persist for a 2-year period without targeted intervention.…”
Section: Introductionmentioning
confidence: 99%